Three Meanings and Three Assumptions of Rationality of Human Action - Horák, Vít (Teorie vědy / Theory of Science, 2009)
This text discusses the notion of rationality with respect to economics. First, it states the essential meanings of this notion and then goes on to the possibilities of rationality, which is a synonym for the effectiveness of human action. It distinguishes three types that may correspond to this meaning, where each type is unique and independent of the other two. In the end, it relates the presented typology to the work of Ludwig von Mises. His radical ap¬proach provides for good instruction of the sides of economic thought that I want to call attention to. Economics as a deductive science is interested in very strong assumptions about human action, and ambiguities about the notion of rationality provide for rhetorical tactics that can justify it. Elucidation of the notion and the presented typology of the meanings and assumptions of ra¬tionality should contribute to the revelation of these tactics.